Space requirements of finishing pigs fed to an average pen weight of 250 pounds - R I Nicholson; G E Fitzner; David A Nichols; Joe D Hancock; Robert H Hines; Robert D Goodband; Jim L Nelssen (Kansas Agricultural Experiment Station Research Reports, 1989)
Space allowances of 6, 8, 10, and 12 ft^2 were evaluated for pigs fed from 130 lb to a pen average of 250 lb. Average daily gain and average daily feed intake. increased linearly (P<.05) as space allowance increased. However, those pigs permitted 10 or 12 ft^2 of space were similar in avg daily gain, avg daily feed intake, and feed efficiency, suggesting that 10 ft^2 of space is adequate for feeding finishing hogs to a heavier average pen weight. Coefficients of variation (CV) for initial weight and final weight were increased for pigs with 6 ft^2, whereas for those exposed to 10 and 12 ft^2, the CV was reduced, indicating more uniform pigs at final weight with greater space allowance.; Swine Day, Manhattan, KS, November 16, 1989
Keywords: Swine day; 1989; Kansas Agricultural Experiment Station contribution; no. 90-163-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 581; Swine; Finishing pig; Space allowance; Heavier weight